Systematic Literature Review (SLR): An In-Depth Review of Robotic Learning with Quasi-Experimental Methods from Pre-School to High School - Dody Hermanto; Didit Ardianto (Universitas Negeri Semarang, 2023)
The increasing presence of robotics in education raises the need for a deeper understanding of the effectiveness of robotic learning. This study focuses on a systematic literature review (SLR) of quasi-experimental robotics learning, ranging from preschool to high school. This research aims to detail and investigate various quasi-experimental approaches in robotics learning, focusing on the age range from preschool to high school and to understand the impact on learners after the robotics learning process. This research uses the SLR approach to collect, evaluate, and synthesize current findings in the literature in the form of articles in reputable international journals spanning the years 2018-2023 regarding quasi-experimental robotics learning. The analysis was conducted to identify common trends, weaknesses, and strengths of the methods applied. The results highlighted the variety of quasi-experimental designs used in robotic learning. Based on 15 articles, 10 used pure Quasiexperimental design, and 5 used Mixed Method. The findings provide an indepth understanding of the effectiveness of the various approaches, enabling robust conclusions to be drawn to improve robotics learning at different levels of education. This review contributes to the literature by identifying new findings using quasi-experimental methods in robotics learning and underresearched research variables. Its significance lies in furthering the understanding of the variables studied and the effectiveness of robotics learning at different stages of education. This research provides a solid knowledge base for developing more effective robotics learning strategies, positively contributing to the advancement of educational science and providing longterm benefits to society by improving the quality of robotics education.